Impact of recombinant expression in Komagataella phaffii on the allergenic properties of the peanut allergen Ara h 2 - Wangorsch, Andrea; Jamin, Annette; Wolfheimer, Sonja; Albrecht, Melanie; Vieths, Stefan; Lidholm, Jonas; Scheurer, Stephan (Frontiers in Immunology, 2025)
IntroductionRecombinant allergens are an important diagnostic tool for determining the IgE-sensitization profile of patients, assessing the risk of symptom severity and potential clinical cross-reactivity. In this context, the use of different host cells for recombinant expression must be evaluated in terms of IgE reactivity and diagnostic value. Therefore, recombinant Ara h 2, the major peanut allergen, was produced in yeast, structurally characterized and investigated in respect to IgE-binding and allergenic properties.MethodsAra h 2 was produced as recombinant protein using yeast and E. coli expression systems. Purified proteins were assessed using SDS-PAGE (reducing and non-reducing conditions), CD-spectroscopy and IgE-reactivity.ResultsRecombinant Ara h 2wt expressed in yeast resulted in an additional predominant band of approximately 12 kDa upon DTT treatment. In contrast, the molecular mass of rAra h 2 expressed in E. coli (Ara h 2E.coli) remained unaffected by reduction. Analysis of rAra h 2wt confirmed the presence of two Ara h 2-derived peptides, one with the expected N-terminus and the other with an N-terminal glycine residue. In silico analysis revealed the presence of a Kex2 cleavage site (R58R59*G60). To test whether Kex2 cleavage affects an IgE-epitope, mutagenesis of this cleavage site from R58 to E58 (Ara h 2mut) was performed. DTT treatment of rAra h 2mut purified from yeast showed that no cleavage of the protein had occurred. No effect on IgE binding could be observed as all rAra h 2 preparations showed IgE-reactivity. Cross-linking of human serum IgE and monoclonal human Ara h 2-specific IgE antibodies showed comparable mediator release in response to Ara h 2wt and rAra h 2mut. However, utilizing a specific combination of human Ara h 2-specific IgE antibodies revealed slight epitope diversity between wildtype and mutated rAra h 2.DiscussionAn endogenous protease, like Kex2 from the expression system, can affect the structural integrity of the target protein, leading to a slightly altered epitope structure. Even this finding has little or no impact for diagnosis, a suitable expression system and a detailed physico- and immunochemical characterization of recombinant allergens prior to their use as a diagnostic tool are of great importance.